Development of a robust video tracking system based on kinect - Tran, Hoai Nam. (2012)
Recently, there has been a proliferation of 3D audio technologies, it has become a challenging task to research and developed new ideas to help out in this area. As a part of a development project in 3D sound systems, one of the most challenging tasks is to locate the position of human ears so that the sound systems could accurately point the sound beam to the ears. As a result, a numerous number of sound effects can be created.